Portable spectroscopic fast neutron probe and He-3 detector dead-time measurements - AKYÜREK, TAYFUN (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
This paper presents dead-time calculations for the Portable Spectroscopic Fast Neutron Probe (N-Probe) using a combination of the attenuation law; MCNP (Monte Carlo N-particle Code) simulations and the assumption of ideal paralyzing and non-paralyzing dead-time models. The N-Probe contains an NE-213 liquid scintillator detector and a spherical He-3 detector. For the fast neutron probe, non-paralyzing dead time values were higher than paralyzing dead-time values, as expected. Paralyzing dead-time was calculated to be 37.6 mu s and non-paralyzing dead-time was calculated to be 43.7 mu s for the N-Probe liquid scintillator detector. Dead-time value for Canberra He-3 neutron detector (0.5NH1/1K) was also estimated using a combination of subcritical assembly measurements and MCNP simulations. The paralyzing dead time was estimated to be 14.5 mu s, and the non-paralyzing dead-time was estimated to be 16.4 mu s for He-3 gas filled detector. These results are consistent with the dead-time values reported for helium detectors. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Dead-time calculations; Attenuation law; MCNP simulations; COUNTERS